Kebun Gizi Sekolahku : Learn,Fun, And Healthy di PKG PAUD Srikandi Kelurahan Sampangan Kecamatan Gajahmungkur Kota Semarang Jawa Tengah - Zainafree, Intan; Budiono, Irwan; Mardiana, Mardiana (Universitas Respati Yogyakarta, 2019)
Riskesdas data in 2013, in Indonesia in the age group above 10 years and less consumption of vegetables and fruits is very high, namely 93.6% of their needs a day. In Central Java, in the age group above 10 years and less consumption of vegetables and fruits reached 91% of their daily needs. The purpose of this research was increasing the consumption of fruits and vegetables for students, increase teacher skills in providing materials related to fruits and vegetables, available school nutrition gardens, available places to teach students to grow crops directly, increase teacher skills in utilizing green houses. All schools in PKG PAUD Srikandi can take part in utilizing my school's nutritional gardens in Labschool PAUD. The methods used educational games about vegetables and fruits, mentoring the preparation of extrafeeding, training in the manufacture of food made from fruits and vegetables, nutritional gardening, revitalization of green house functions, fruit and vegetable education packages, balanced nutrition training for children for parents and teachers. The results showed there were nutritional gardens, hydroponic plants, increased teacher skills about vegetables and fruits, 90% of students liked vegetables and fruit,Â increased parental participation related to the provision of healthy supplies to children in school, menu books for extrafeeding schools. The conclusions are increasing in vegetable consumption and can be realized by involving parents, teachers, and children. The need for vegetables and fruits can be met at school and at home.Keywords: Nutrition garden, Hydroponics, Vegetables, Fruit, PAUD